Assessment of poultry waste management in Trishal upazila, Mymensingh - Hossen, Md Shahadat; Hoque, Ziaul; Nahar, Begum Samsun (Research in Agriculture Livestock and Fisheries, 2015)
A study was conducted to assess the present status of poultry waste management by poultry farmers in Trishalupazila of Mymensingh district, Bangladesh during July to November 2013. A structured, pre-tested questionnaire was used for collecting data. The highest 52% respondents were involved in layer farming and majority of the respondents did not use any litter materials where 36% and 12% used rice husk and sawdust respectively as litter. The availability of storage and treatment facilities was in 24% farms but their storage system was uncovered. Fifty per cent of the farmers sold their litter while some other used as fish feed, soil amendment and for biogas production. Only 16% farmers faced diseases related to poultry waste and the rest (84%) never faced any disease. It was noticed that 54% farmers faced environmental problems and 46% were unconcerned about environmental problem. They considered odor, flies and mosquitoes and leaching as environmental problem. Only 24% farmer mentioned financial problem as barrier of poultry waste management and majority claimed about unconsciousness. It is concluded that poultry waste management by farmers in the study area is inefficient, implying inadequate awareness of the potential negative impact of poor handling of poultry wastes. More extensive work is required to trainup the poultry farmer for proper handling and utilization of poultry wastes. Res. Agric., Livest. Fish.2(2): 293-300, August 2015